HYDROGEOLOGY AND GROUNDWATER QUALITY IN THE SOUTHEASTERN SLOPE OF MOUNT MALABAR, WEST JAVA - Estuaji, Enggal
As the third largest river in Java, Citarum River is a source of water supply that sustains domestic, agricultural, and industrial activities for 25 million people. In 2018, the Citarum River received the title as one of the most polluted rivers in the world. This research was conducted to find out the geological conditions, hydrogeology, and groundwater quality in the southeastern part of the slopes of Mount Malabar which is the upstream area of the Citarum River. With geological mapping and groundwater observations on an area of 72km2, groundwater data obtained is checked with Permenkes standard number 492 of 2010 on Drinking Water Quality Standards and analysis of groundwater contamination vulnerability index based on Ribeiro (2000). Geomorphology of the research area consists of 10 units with its type is the inter-volcanic plain, inter-volcanic valley, volcanic cones, and pyroclastic ridges. The research area is divided into 20 geological units with the type of units in the form of pyroclastic flows, lahar flow, pyroclastic falls, lava flows, and lava domes. There is a primary structure in the form of sheeting joints and a secondary structure in the form of a fault in the research area. Hydrogeology of the research area is divided into 4 aquifers and 2 aquiclude with the type of rock in the form of volcanic tuff, pyroclastic breccia, laharic breccia, and andesite. The results of the groundwater quality analysis obtained 38 points of the study with a range of pH values of 1.46-7.7 and TDS values of 12-779, with the distribution of 14 springs meeting pH standards and 37 springs meeting TDS standards. In addition, there is also a groundwater contamination susceptibility index in the area with 10% of which is very low, 16% low, 34% moderate, 37% high, and 3% very high. Then, the data was validated by the correlation of the vulnerability index to pH levels, SO4 2-, and Na+ levels that showed low, high, and moderate values consecutively. Finally, it is estimated that the value of the high dominant vulnerability index in the research area may be due to geochemical processes and plantation activity.